Percutaneous Mitral Edge-to-Edge Repair: State of the Art and a Glimpse to the Future - Khan, Faisal; Winkel, Mirjam; Ong, Geraldine; Brugger, Nicolas; Pilgrim, Thomas; Windecker, Stephan; Praz, Fabien; Fam, Neil (Frontiers in Cardiovascular Medicine, 2019)
Patients with severe symptomatic mitral regurgitation have a poor prognosis if left untreated. In those patients who are not eligible for mitral valve surgery, percutaneous edge-to-edge repair may improve clinical outcomes. Recent clinical trials have added to our knowledge and provide interesting insights into the management of such patients. With an increasingly aging global population, these technologies are likely to represent an important treatment option. This mini-review will examine the technology, the evidence and the latest developments in the Percutaneous mitral edge-to-edge repair.